Pengaruh Paparan Kebisingan di Tempat Kerja terhadap Risiko Benign Paroxysmal Positional Vertigo (BPPV): Suatu Tinjauan Naratif - Ayu Zahrani; Tishya Fadiliafasha; Alif Rachman Chresandiputra; Najwa Chindykia Yuliasta; Moch Althof Naufal Ardhi; Yusuf Alam Romadhon (Pusat riset dan Inovasi Nasional, 2026)
Benign Paroxysmal Positional Vertigo (BPPV) is the most common cause of peripheral vertigo, characterized by brief episodes of vertigo due to otoconia displacement. Although most previous studies have focused on intrinsic factors such as age, gender, osteoporosis, and metabolic disorders, evidence regarding the role of environmental factors, particularly occupational noise exposure, is limited. Chronic noise has the potential to affect vestibular function through both sensory and vascular mechanisms. This study aims to narratively review the effect of occupational noise exposure on the risk of BPPV by integrating clinical, epidemiological, and experimental findings. The method used is a literature-based narrative review of the PubMed, Scopus, Web of Science, and Google Scholar databases without year restrictions, using the keywords